Unsupervised vector-based classification of single-molecule charge transport data - Mario Lemmer (Nature Portfolio, 2016)
The stochastic nature of single-molecule charge transport measurements requires collection of large data sets to capture their full complexity. Here, the authors adopt strategies from machine learning for the unsupervised classification of single-molecule charge transport data without a prioriassumptions.